USAGE OF VIDEO GAMES AS COGNITIVE EXERCISE AND ITS INFLUENCE ON EDUCATION AMONG ADULTS (A CASE STUDY OF MULTAN DISTRICT) - Mushtaq Naz; Amna Mushtaq; Ayesha Sajid Taga; Kamran Ishfaq; Muhammad Shoaib (International Journal of Contemporary Issues in Social Sciences, 2023)
The study explores the repercussions of Usage of Video Games as cognitive exercise and Its Influence on Education among Adults in District Multan. Video games, characterized as interactive multimedia forms of entertainment experienced on various digital platforms, are scrutinized for their potential to disrupt adults’ concentration on academic tasks. A substantial proportion of participants in the study strongly concurred that video games had deleterious effects on their mental health. This research underscores the urgent need to enhance awareness of the psychological consequences associated with excessive gaming among the student population, the study scrutinizes the prevalent patterns of video game consumption among adults in District Multan and evaluates adults’ academic achievements as a cognitive exercise in relation to their engagement with video games. Understanding the intricate relationship between gaming and Education, it carries manifold significance. It offers invaluable insights for educators and policymakers seeking to navigate the impact of video games on adults in District Multan, A selection of 200 respondents (Students) as sample size using a simple random sampling technique targeted. Data collected via a self-administered questionnaire designed to assess the effects of video games. Data analyzed by using SPSS (Statistical Package for the Social Sciences), incorporating descriptive statistics, Current study illuminates a negative correlation between video games and both Education and health. Adults expressed that video games hindered their ability to concentrate on schoolwork and adversely affected their mental health. Further investigations are warranted to delve into the impact of video game consumption on adults’ time management skills and study habits, Potential adverse consequences video games as cognitive exercise on the Education and mental well-being of adults in District Multan. It accentuates the imperative for ongoing exploration of this subject to advance a more inclusive thoughtful of the trials posed by extensive gaming among the student demographic.